(untitled) (KULT_online, 2009)
Editors Bayerdörfer, Fischer, and Halbach from the Institute for Theatre Studies of Ludwig-Maximilians-University in Munich assemble in their volume Judenrollen (Jewish Roles) 21 essays on the depiction of Jews in European theatre from the Restauration through the post-WWI era. There are not only analyses of theatre pieces like Albert Dulk’s Lea or Arthur Schnitzler’s comedy Professor Bernhardi, but also works of opera like those by Hans Pfitzner or Vincent d’Indy. The question how Jewish figures appear on stage is shown in its connection to the epoch which spans from the beginning of Jewish emancipation in Germany to its cancellation by the national socialists. Important questions are: which possibilities are available for Jewish figures, from which positions they are kept away, and which changes in their role profile are imposed on them. All in all, the present volume displays the various and multifaceted careers of Jewish figures in opera and theatre of the 19th and 20th centuries.